담낭 용종성 병변의 임상 양상과 수술 적응증 - 도영우(Young Woo Doh); 이정효(Jung Hyo Lee); 임현묵(Hyun Muk Lim); 지경천(Kyung Chun Chi); 박용검(Yong Gum Park) (Annals of surgical treatment and research, 2005)
Purpose: Polypoid lesions of the gall bladder (PLG) have a variety of pathologies. Problems exist in the selection of patients for operation and in the operative approach used. We studied the accuracy of the preoperative radiologic diagnosis and suspected risk factors. Methods: 121 polypoid lesions of gallbladder were sugically treated during 10 years. Preoperative radiologic diagnosis, age, gender, related symptoms, concurrent gallstone, size, shape, number and histologic diagnosis of the ployps were retrospectively reviewed. Results: The average size of malignancy was 23.0 mm, and that of benign tumors was 7.1 mm (P=0.000). The mean age of patients with a malignancy was significant higher than that of those with benign tumor (P=0.000). The preoperative sensitivity of computed tomography for a malignancy was 67.7%. The patients with malignancy more frequently had related symptoms. Conclusion: A CT must be considered, for patients with risk factors, even if the ultrasonographic diagnosis was benign. An Age greater than 60 years, a tumor size greater than 10 mm, a solitary polyp, sessile shape, and related symptoms are predictive factors of a malignancy. KCI Citation Count: 3